Slow Violence and Precarious Progress: Picturebooks About Wangari Maathai - Moriarty, Sinéad (Humanities (Basel), 2025)
Rob Nixon in his 2011 book Slow Violence and the Environmentalism of the Poor writes “[i]n a world permeated by insidious, yet unseen or imperceptible violence, imaginative writing can help make the unapparent appear” (p. 15). Nixon talks about the power of literature to render spectacular environmental violence which has become mundane and thus largely invisible. He points to the writing of Kenyan environmentalist and politician Wangari Maathai as work which captures the notion of slow violence. In her writing, Maathai creates the sense of urgency that Greta Gaard argues is a key boundary condition for an ecopedagogy of children’s literature. This article explores seven illustrated biographies of Maathai. The article interrogates the extent to which the books capture what Rob Nixon describes as “slow violence”, that is violence that occurs slowly, over time, and which is often overlooked. The article also introduces the term precarious progress to describe the fragile nature of the change initiated after slow violence. Finally, the article also draws on Val Plumwood’s writing on place attachment and “shadow places” to explore how the Kenyan landscape is depicted as not mere object but subject in these texts and the way in which they work to foster a consciousness of place in their child readers.